Genome-wide identification and characterization of BASIC PENTACYSTEINE transcription factors and their binding motifs in coconut palm - Lao, Zifen; Mao, Jiali; Chen, Runan; Xu, Ran; Yang, Zhuang; Wang, Ying; Zhou, Junjie; Mu, Zhihua; Xu, Hang; Li, Fengmei; Huang, Dongyi; Xiao, Yong; et al. (Frontiers in Plant Science, 2024)
Introduction BASIC PENTACYSTEINE (BPC) is a small transcription factor family known for its role in various developmental processes in plants, particularly in binding GA motifs and regulating flower and seed development. However, research on the functional characteristics and target genes of BPCs in coconut (Cocos nucifera) is limited. Methods In this study, we systematically characterized the gene structure, conserved protein domains, gene expansion, and target genes of CnBPCs in the coconut genome. We conducted yeast one-hybrid (Y1H) and dual-luciferase assay to explore gene interactions. We identified genes with the GA motif in their promoter regions and combined this information with a weighted gene co-expression network to identify the target genes of CnBPCs. Results Eight CnBPCs were identified, including three Class I CnBPCs from triplication, four Class II CnBPCs (with CnBPC6A and CnBPC6B resulting from segmental duplication), and one Class III CnBPC (CnBPC7). Three conserved DNA-binding motifs were detected, exhibiting variation in certain sites. Widespread BPC gene expansion was detected in coconut and other plant species, while only three BPCs were found in the most basal extant flowering plant. Notably, 92% of protein-coding genes contained at least one GA motif, with the (GA)3 motif being most prevalent. Genes containing the GA motif that exhibit a high expression correlation with CnBPCs, tend to interact strongly with the corresponding CnBPCs. Additionally, promoters rich in the GA motif tend to interact with all members of CnBPC. The dual-luciferase assay showed that CnBPCs could activate or repress the transcriptional activities of promoters containing either (GA)3 or (GA)11 motif but with a bias toward certain genes. Furthermore, we constructed co-expressed networks identifying 426 genes with GA motifs as potential CnBPC targets. Discussion Our findings suggest that CnBPCs may play significant roles in seed germination, flower development, and mesocarp development by interacting with genes such as CnAG1, CnAG2, CnSTK, CnMFT, and CnCS. This study characterized CnBPCs’ binding motif and possible target genes, laying a theoretical foundation to reveal CnBPCs’ function in flower and seed development.